Indicadores de sustentabilidade no segmento de distribuição de energia - Santos, Fábio Lira (2019)
The present study seeks to develop a tool for measuring the level of sustainability in an effective and quantitatively comparable way for electricity distribution companies, based on the dashboard of sustainability, composed of 17 indicators, in the social, environmental and economic dimensions, using as data source their balance sheets and corporate statements. The sample of the analysis was made of distributors from nine states in the northeastern region of Brazil - Coelba (BA), Energisa (SE), Eletrobras (AL), celpe (PE), Energisa (PB), Cosern (RN), Enel (CE), Eletrobras (PI), Cemar (MA). Values from data were calculated for each distributor and the degree of sustainability of these companies was calculated. The results show large differences in their levels of sustainability, both general and in each of the dimensions. Cosern (RN) presented the best levels with a "good" classification. Most were “average” or “reasonable”. In the economic aspect, the distributors still recover from a strong moment of financial crisis due to recent state tariff policies, being worrisome for strategic and economic role of this sector. We also noticed a lack of uniformity in the data presented in the statements, which implies methodological obstacles to comparative analysis. However, the tool proved effective; demonstrating differences between companies in their various dimensions, being efficient and practical in their use.